UTILIZING JOLLY PHONICS SONGS AND FLASH CARDS TO TEACH IRAQ EFL PRIMARY SCHOOL PUPILS’ LANGUAGE LEARNING SKILLS - Lect. Noor Hameed Majeed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current study aims at finding out the effect of utilizing Jolly phonics songs and flash cards to teach Iraq EFL primary school Pupils’ language learning skills. Therefore, the researcher used the experimental design and post-test as a data collection tool. Two groups of first class primary school pupils, experimental and control, were selected to be the sample of this study, which consists of (36) students in each group during the academic year 2018/2019. The two groups were equalized in terms of many several variables that may effect on the independent variable (Jolly phonics songs and flash card). Then, suitable statistical tools were applied on analyzing the data and to achieve the aim of this study. The findings of this study showed that jolly phonics songs and flash card has effectively improved the students’ language learning skills since that there is a statistically difference in EFL students’ oral achievement in favor of the post-test scores of the experimental group. Based on the results obtained, a set of conclusions are put forward.